Tectonics and Structural Geology: Indian Context - Mukherjee, Soumyajit (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents a compilation of findings, review and original works, on the tectonic evolution and structural detail of several terrains in India. It captures the tectonic diversity of the Indian terrain, including tectonics of India's coastal areas, the tectonic evolution of Gondwana and Proterozoic (Purana) basins. It also describes the research results of the Indian craton's geo-history, Tertiary Bengal basin, and also the Himalayan collisional zone. Thus the book covers the deformation history of Indian terrain involving strike slip, compressional and extensional tectonics, and ductile and brittle shear deformations.
Proterozoic Crustal Evolution of the Chotanagpur Granite Gneissic Complex, Jharkhand-Bihar-West Bengal, India: Current Status and Future Prospect -- Geomorphic characteristics and morphologic dating of the Allah Bund Fault scarp, Great Rann of Kachchh, Western India -- Interplay between tectonics and eustacy in a Proterozoic epicratonic, polyhistory basin: Kaladgi basin, north Dharwar craton -- NE-SW Strike-slip fault in the granitoid from the margin of the South East Dharwar Craton, Degloor, Nanded district, Maharashtra, India -- Synthesis of the Tectonic and Structural Elements of the Bengal Basin and its Surroundings -- Fold-thrust belt architecture and structural evolution of the Northern part of the Nallamalai Fold Belt, Cuddapah basin, Andhra Pradesh, India -- Tectonic history of the granitoids and Kadiri schist belt in the SW of Cuddapah basin, Andhra Pradesh, India -- Basement Tectonics and Shear Zones in Cauvery Basin (India): Implications in Hydrocarbon Exploration -- Implication of transfer zones in rift fault propagation: Example from Cauvery basin, Indian east coast -- Remote sensing, structural and rock magnetic analyses of the Ramgarh structure of SE Rajasthan, Central India- Further clues to its impact origin and time of genesis -- Geology, Structural Architecture and Tectonic Framework of the Rocks of Southern Lalitpur District, Uttar Pradesh, India: An Epitome of the Indian Peninsular Shield -- Deformation in the Kangra Reentrant, Himachal Pradesh of NW-Sub Himalaya of India: A paradox -- Impact of Structural Damage Zones on Slope Stability: A case study from Mandakini Valley, Uttarakhand state (India) -- Documentation of brittle structures (back shear and arc-parallel shear) from Sategal and Dhanaulti regions of the Garhwal Lesser Himalaya -- Field structural geological studies around Kurseong, Darjeeling-Sikkim Lesser Himalaya, India -- Pb - isotopic characterization of major Indian Gondwana Coalfields: Implications for environmental fingerprinting and Gondwana reconstruction.
Description based on publisher-supplied MARC data.
Keywords: Economic geology; Geophysics; Mineralogy; Structural geology; Structural Geology; Economic Geology; Geophysics/Geodesy.; Mineralogy